AN ANALYSIS OF THE RELEVANCE OF INSTRUCTIONAL MATERIALS AND THE TYPE OF TEACHING STRATEGIES USED FOR READING 3 COURSE IN ENGLISH EDUCATION DEPARTMENT - ., I Gusti Ayu Dwi Parwiti; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This research was conducted to analyze the relevance of instructional materials and the types of teaching strategies used for Reading 3 course in English Education Department. The purpose was to find the data about the syllabus used by the lecturers and its development and analyze the relevance of the instructional materials used in Reading 3 course with the syllabus, the type of teaching strategies employed by the lecturer in teaching Reading 3 course, and the students perception about the material development and teaching strategies used in Reading 3 course. The subjects of the study were the lecturer and students in Reading 3 course of English Education Department, Ganesha University of Education. This research was a descriptive qualitative research which was utilizing checklist and questionnaires. The data collected from the lecturers and expert judgesâ€™ checklist, as well as lecturers and studentsâ€™ questionnaire. The data obtained were descriptively analyzed. The findings of the research showed Reading 3 syllabus was not optimally prepared by each lecturer at English Education Department that was obtained from the questionnaire filled out by the lecturers and the result of Focus Group Discussion with the students. Then, the relevance of Instructional Materials and the Reading 3 syllabus was said â€œNot Relevantâ€ to be used as learning resource for English Education Department students. In teaching strategy, there were 5 teaching strategies which were used frequently in Reading 3 course namely Direct Instructions, Discussion, Small Group Work, Cooperative Group, and Using Inquiry Based Learning. Based on focus group discussion there was no clear focus on learning objectives and skills to be achieved in the Reading 3 course.keyword : reading skill, early advanced level, instructional material, relevance material, and teaching strategies.